Floating elbow combining ipsilateral distal multiple segmental forearm fractures: A case report - Huang, Guo-Hua (World J Clin Cases, 2021)
BACKGROUND: Floating elbow along with ipsilateral multiple segmental forearm fracture is a rare and high-energy injury, although elbow dislocation or fracture of the ulna and radius may occur separately. CASE SUMMARY: We report the case of a 37-year-old woman with open (IIIA) fracture of the right distal humerus with multiple shaft fractures of the ipsilateral radius and ulna with a history of falling from a height of almost 20 m from a balcony. After providing advanced trauma life support, damage control surgery was performed to debride the arm wound and temporarily stabilize the right upper limb with external fixators in the emergency operating room. Subsequently, one-stage internal fixation of multiple fractures was performed with normal values of biochemical indicators and reduction in limb swelling. The patient achieved good outcome at the 7 mo follow-up. CONCLUSION: One- or two-stage treatment must be performed according to the type of injury; we efficiently used the “damage control principle.”